First, multiply 4*2x-4*-5= 8x-20.
Second, add 15 to 8x-20
Third, that would equal 8x-20+15=11
Fourth, 15+-20= -5
Fifth, 8x-5=11
Sixth, add +5 to -5 and +5 to 11= 8x=16
Last, do 8x/8x and 16/8x
The answer is x=2
![\bold{\huge{\orange{\underline{ Solution }}}}](https://tex.z-dn.net/?f=%5Cbold%7B%5Chuge%7B%5Corange%7B%5Cunderline%7B%20Solution%20%7D%7D%7D%7D)
<h3><u>Correct </u><u>Question </u><u>:</u><u>-</u></h3>
What is the 5th term of an AP 2 , 14 ....98 .
<h3><u>Given </u><u>:</u><u>-</u><u> </u></h3>
<u>We </u><u>have </u><u> </u><u>AP</u><u>, </u>
![\sf{ 2 , 14 ,.... 98 }](https://tex.z-dn.net/?f=%5Csf%7B%202%20%2C%2014%20%2C....%2098%20%7D)
- <u>AP </u><u>is </u><u>the </u><u>arithmetic </u><u>progression </u><u>or </u><u>a </u><u>sequence </u><u>of </u><u>numbers </u><u>in </u><u>which </u><u>succeeding </u><u>number </u><u>is </u><u>differ </u><u>from </u><u>preceeding </u><u>number </u><u>by </u><u>a </u><u>common </u><u>value</u><u>. </u>
<h3><u>Solution </u><u>:</u><u>-</u></h3>
<u>We </u><u>have </u><u>an </u><u>AP </u><u>:</u><u>-</u><u> </u><u>2</u><u> </u><u>,</u><u> </u><u>1</u><u>4</u><u> </u><u>.</u><u>.</u><u>.</u><u>.</u><u>.</u><u>9</u><u>8</u>
<u>Therefore</u><u>, </u>
<u>Here</u><u>, </u>
Common difference of an AP
![\sf{ a2 - a1 }](https://tex.z-dn.net/?f=%5Csf%7B%20a2%20-%20a1%20%7D)
![\sf{ = 14 - 2}](https://tex.z-dn.net/?f=%5Csf%7B%20%3D%2014%20-%202%7D)
![\sf{ = 12}](https://tex.z-dn.net/?f=%5Csf%7B%20%3D%2012%7D)
Thus, The common difference is 12
<u>Now</u><u>, </u>
We know that,
![\sf{an = a1 + ( n - 1 )d}](https://tex.z-dn.net/?f=%5Csf%7Ban%20%3D%20a1%20%2B%20%28%20n%20-%201%20%29d%7D)
![\sf{a5 = 2 + ( 5 - 1 )12}](https://tex.z-dn.net/?f=%5Csf%7Ba5%20%3D%202%20%2B%20%28%205%20-%201%20%2912%7D)
![\sf{a5 = 2 + 4 × 12}](https://tex.z-dn.net/?f=%5Csf%7Ba5%20%3D%202%20%2B%204%20%C3%97%2012%7D)
![\sf{a5 = 2 + 48}](https://tex.z-dn.net/?f=%5Csf%7Ba5%20%3D%202%20%2B%2048%7D)
![\sf{\red{a5 = 50}}](https://tex.z-dn.net/?f=%5Csf%7B%5Cred%7Ba5%20%3D%2050%7D%7D)
Hence, The 5th term of given AP is 50
Answer:
5555555555555555555225313
Step-by-step explanation:
3
6
554
The first term of this sequence is -20, and the common ratio is 11. Thus, the formula for the nth term is
a(n) = a(1)*(11)^(n-1), or (-20)*(11)^(n-1).
Thus, the 12th term is
a(12) = (-20)*(11)^(12-1) = -20(11)^11 = -20(2.85 times 10 to the 11th power.
or ... -5.71 times 10 to the 12th power.
The answer is D because if you plug in the ordered pair in their correct places the equation becomes 4+6=10.